2002
DOI: 10.1002/1615-9861(200209)2:9<1169::aid-prot1169>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic study of a model causative agent of harmful red tide, Prorocentrum triestinum I: Optimization of sample preparation methodologies for analyzing with two-dimensional electrophoresis

Abstract: A comprehensive study to find the optimal sample preparation conditions for two-dimensional electrophoresis (2-DE) analysis of Prorocentrum triestinum, a model causative agent of harmful algal blooms (HABs) was carried out. The four major sample preparation steps for 2-DE: (a) cell disruption: i.e. sonication and homogenization with glass beads; (b) protein extraction : i.e. sequential and independent extraction procedures; (c) pre-electrophoretic treatment: these included (i) treatment with RNAase/DNAase or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 9 publications
(15 reference statements)
3
50
0
Order By: Relevance
“…The most common methods of protein purification rely on selective precipitation. Acetone, trichloroacetic acid (TCA), and other precipitation methods can be performed, and a number of commercially available kits make this a routine procedure (12,13). In some instances though, pure protein may not be sufficient because proteins such as IgGs or albumin constitute the vast majority of protein concentrations in cells.…”
Section: Sample Preparationsupporting
confidence: 84%
“…The most common methods of protein purification rely on selective precipitation. Acetone, trichloroacetic acid (TCA), and other precipitation methods can be performed, and a number of commercially available kits make this a routine procedure (12,13). In some instances though, pure protein may not be sufficient because proteins such as IgGs or albumin constitute the vast majority of protein concentrations in cells.…”
Section: Sample Preparationsupporting
confidence: 84%
“…In another dinoflagellate species, Gambierdiscus toxicus, CDK2 was found to be expressed throughout the whole cell cycle, but it was active only at the later dark phase [9]. A few other CDKs have also been detected in eukaryotic cells that cause HABs [12,19]. These results indicate that, by modulating the cell cycle, cyclins and CDKs may play important roles in regulating cell growth and HABs.…”
Section: Differential Protein Expression Patterns In a Catenella Durmentioning
confidence: 94%
“…In contrast to conventional biochemical approaches that address one or a few specific proteins at a time, proteomic techniques allow the simultaneous isolation and identification of hundreds or thousands of proteins in one sample. In the past few years, the proteomic approach has been used to study dinoflagellates, and a few important functional proteins have been identified and characterized [19][20][21][22][23].…”
mentioning
confidence: 99%
“…Dinoflagellate proteomics is still a new field, with a very small number of expressed proteins described (Chan et al 2002). To our knowledge only one laboratory has successfully applied such methodology to the study of this group of algae.…”
Section: Proteomicsmentioning
confidence: 99%
“…(Chan et al 2002), using two-dimensional gel electrophoresis (2-D) analysis for dinoflagellate species recognition (Chan et al 2004) and to detect biomarkers of toxicity (Chan et al 2005b). …”
Section: Introductionmentioning
confidence: 99%